Penerapan Model Problem Based Learning dan Model Project Based Learning terhadap Hasil Belajar Siswa - Effendi Effendi; Melvi Sugiarti; Wahid Gunarto (SPEJ (Science and Physic Education Journal), 2019)
The purpose of this study is to find out whether there are significant differences in learning outcomes between students whose learning uses PBL learning models with PjBL learning models in the Vibration and Wave material in Class VIII Belitang Madang Raya 3 Middle School Learning Year 2017/2018. The type of research used in this study is quantitative research methods. The population in this study were class VIII students in the Belitang State Junior High School 3 in Madang Raya consisting of 6 classes. The sampling technique in this study was carried out in a random manner through drawing existing classes. Data collection techniques to find out the learning outcomes of students using tests, and testing hypotheses using the z-test. Based on student learning outcomes after the test is obtained the average value of the experimental class I is 81.88 and the average value of the experimental class II is 73.2. There are significant differences in learning outcomes between students whose learning uses the PBL learning model with the PjBL learning model in the material of Vibration and Waves in Class VIII of the State Middle School 3 Belitang Madang Raya Learning Year 2017/2018. This can be seen from the value of Zhit = 39.3 not located between -1.96 and 1.96, so that H0 is rejected and Ha is accepted. Keywords: Problem Based Learning, Project Based Learning, Student Learning Outcomes.